Retrograde Approach to a Diverticular Kidney Stone through a Vesicoureteral Cohen's Reimplantation: A Novel Surgical Technique - Fahd Khalil; Mohamed Tligui; Olivier Traxer (Case Reports in Urology)
Cohen's technique is the standard treatment of vesicoureteral reflux in children. Its disadvantage is still the classic difficulty in subsequent retrograde ureteral access, requiring the use of percutaneous techniques in the treatment of kidney stones. We describe a novel surgical technique for retrograde catheterization of an adult ureter by a flexible ureterorenoscope, thereby facilitating the treatment of a symptomatic diverticular kidney stone. We compare our technique to other methods described in the literature.